Slow spin relaxation and low-temperature spin freezing in the disordered fluorite Ho₂Zr₂O₇ - Elghandour, Ahmed; Sheetal; Yadav, C. S.; Klingeler, Rüdiger (Physical review. B, Condensed matter and materials physics, 2024)
We report on the origin of spin freezing in the disordered fluorite Ho₂Zr₂O₇. The system is investigated by low-temperature heat capacity as well as by dc and ac magnetization. While the system does not show a long-range magnetic order down to at least 𝑇=280 mK, we observe signatures of slow spin dynamics, magnetic-field-induced relaxation processes at relatively high temperatures, and a spin-frozen state below 𝑇=0.6 K. Our results suggest that similar to the canonical spin-ice systems Ho₂Zr₂O₇ [J. Phys.: Condens. Matter 16, S635 (2004)] and Dy2⁢Ti2⁢O7 [Nature (London) 413, 48 (2001)], spin freezing in Ho₂Zr₂O₇ is preceded by two slow spin-relaxation processes; the first forms a field-induced region extending to at least 18 K and the second is rather field independent and appears at 𝑇g⁡2=1 K [J. Ramón, Ph.D. thesis, Universidade de São Paulo (2020)].